Ієрархічність соціальних процесів та асиметрія взаємодії між ними - Грушко, Віктор Сергійович; Грушко, Виктор Сергеевич; Hrushko, Viktor S. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У роботі виокремлено головні динамічні рівні в ієрархічності процесів, з’ясувано особливості кожного з них та специфіку взаємодії між різноповерховою динамікою, виявлено фактори, які володіють здатністю односторонньо піддавати змінам інших (чи послаблювати їхню дію) й одночасно мінімально зазнавати зворотних впливів (або ж узагалі не піддаватися їм). Обґрунтовано провідну роль у суспільстві таких впливових рівнів, як несвідоме, культура, цивілізація, уявне ідеальне та виявлено пріоритетність останнього. Виявлено визначальну роль знакової системи в становленні культури й цивілізації, у побудові стратифікаційної структури суспільства та регулюванні багаторівневої соціальної динаміки. Research is devoted to the analysis of the hierarchy of processes that unfold in society, singling out in it the main dynamic levels, identifying the characteristics of each of them and the specific interactions between diverse dynamics, identify the factors that are most able to unilaterally change the surrounding social space (or weaken the effects of other forces in it) and thus at least suffer losses reverse influence (or to be not subjected it). Attention is paid to such important levels, as the unconscious, cul-ture, civilization, imaginary perfect and proved the key role of the latter. An important place in the article is given the role of the characters in the allocation of human society and the natural environment in the organization of complex social systems. The relationship of a sign with information, draws attention to its decisive role in the formation of the human mind, in the development of culture in the development of civilization in the construction of the stratification of the hierarchical structure of society. Reveals the mechanisms of constructing complex societies with different sign systems and the peculiarities of their functioning. Attention is drawn to the work on the conflict generated by the diversity of different planes and proved the key role of the latter.
Hierarchical Social Processes and Asymmetry of the Interaction between Them
Keywords: несвідоме; культура; цивілізація; соцієтальні утворення; ідеали; сенси життя; unconscious; culture; civilization; societal movements; ideals; sense of life